A brief history of population genetic research in California and an evaluation of its utility for conservation decision-making. (30th November 2022) - Beninde, Joscha; Toffelmier, Erin; Shaffer, H Bradley
Abstract: A recently published macrogenetic dataset of California's flora and fauna, CaliPopGen, comprehensively summarizes population genetic research published between 1985 and 2020. Integrating these genetic data into the requisite "best available science" upon which conservation professionals rely should facilitate the prioritization of populations based on genetic health. We evaluate the extent to which the CaliPopGen Dataset provides genetic diversity estimates that are 1) unbiased, 2) sufficient in quantity, 3) cover entire species' ranges, and 4) include potentially adaptive loci. We identified genetic diversity estimates for 4, 462 spatially referenced populations of 432 species, confirming California's rich published history of population genetics research. Most recent studies used microsatellites markers, which have uniquely high levels of variation, and estimates of all genetic metrics varied significantly across marker types. Most studies used less than 10 loci for inferences, rendering parameter estimates potentially unreliable, and covered small spatial extents that include only a fraction of the studied species' California distribution (median 16.3%). In contrast, the ongoing California Conservation Genomics Project (CCGP) aims to cover the full geographical and environmental breadth of each species' occupied habitats, and uses a consistent approach based on whole-genome data. However, the CCGP will sequence only 12% of the number of individuals, and covers only about half the evolutionary diversity, of the CaliPopGen Database. There is clearly a place in the evaluation of the genetic health of California for both approaches going forward, especially if differences among studies can be minimized, and overlap emphasized. A complementary use of both datasets is warranted to inform optimal conservation decision-making. Finally, a synopsis of the available population genetic data for California, all other US states and 241 other countries, allows us to identify states and countries for which meaningful data summaries, such as CaliPopGen, could be collated and others, which have limited published data available and are prime targets for future, empirical work.